P490 Drug survival and immunogenicity after switching from Remicade® to biosimilar CT-P13 in inflammatory bowel disease patients: Two-year follow-up of a prospective observational cohort study. (16th January 2018) - Smits, L; Derikx, L; van Esch, A; Drenth, J; Boshuizen, R; de Jong, D; Hoentjen, F
Abstract: Background: The infliximab biosimilar CT-P13 is widely implemented in current daily IBD practice in most European countries. Several studies showed reassuring data on switching from Remicade ® to CT-P13 in IBD patients. However, long-term outcomes beyond 1 year are scarce, especially pharmacokinetic and immunogenicity data are lacking. We previously reported 1-year data from our cohort of IBD patients who switched to CT-P13. Our current aim was to investigate the long-term drug survival, pharmacokinetics and immunogenicity 2 years after switching to CT-P13. Methods: We performed a single-centre prospective observational cohort study in all Remicade ® -treated IBD patients who switched to CT-P13 in 2015. Primary endpoint was drug survival at Week 104 and reasons for discontinuation. We systematically documented trough levels and anti-drug antibodies to infliximab (ADA) at baseline, Week 52 and Week 104. Furthermore, biochemical and clinical disease activity were registered by measuring C-reactive protein (CRP), faecal calprotectin (FCP), Harvey–Bradshaw Index (HBI) for Crohn's disease (CD) and Simple Clinical Colitis Activity Index (SCCAI) for ulcerative colitis (UC) and IBD unclassified (IBD-U). Results: Eighty-three patients were enrolled, 57 with CD, 24 with UC and 2 with IBD-U (28 male, median age 36, IQR 27–51). At Week 104, 53 of 78 (68%) patients remained on CT-P13 while 5 were lost to follow-up. Reasons for discontinuation during Years 1 and 2 were disease remission ( n = 2 and 5), loss of response ( n = 5 and 5) and adverse events ( n = 6 and 2) (Figure 1). Median trough levels at baseline, Weeks 52 and 104 were 3.6 μg/ml [IQR 1.7–5.5], 3.7 μg/ml [IQR 2.1–5.8] and 3.9 μg/ml [IQR 2.2–5.7] ( p = 0.664). During Year 2, dosing was increased in 14 of 53 (26%) patients, due to low trough levels ( n = 5), disease activity ( n = 4) or both ( n = 5). Dosing was decreased in 5 of 53 (9%) patients, due to supra-therapeutic trough levels ( n = 2), remission ( n = 2) or both ( n = 1). ADA were present in 5 of 83 patients at baseline (prior to switching), in 2 patients before Week 52, and no subsequent ADA were detected until Week 104. HBI, SCCAI, FCP and CRP levels did not significantly change during the 104-week follow-up. Conclusions: In a prospective cohort with >2-year follow-up, 68% of IBD patients continued CT-P13 beyond 2 years after switching from Remicade ® . Main reasons for discontinuation were loss of response, adverse events and stable disease remission. Two new cases with ADA were observed in Year 1, but no immunogenicity was detected beyond Week 52.